2008
DOI: 10.1152/ajpendo.90477.2008
|View full text |Cite
|
Sign up to set email alerts
|

Impaired microvascular perfusion: a consequence of vascular dysfunction and a potential cause of insulin resistance in muscle

Abstract: Insulin has an exercise-like action to increase microvascular perfusion of skeletal muscle and thereby enhance delivery of hormone and nutrient to the myocytes. With insulin resistance, insulin's action to increase microvascular perfusion is markedly impaired. This review examines the present status of these observations and techniques available to measure such changes as well as the possible underpinning mechanisms. Low physiological doses of insulin and light exercise have been shown to increase microvascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(210 citation statements)
references
References 184 publications
(272 reference statements)
8
191
1
6
Order By: Relevance
“…In addition to total limb blood flow, another mediator of insulin and AA delivery to the muscle is the distribution of blood flow between so-called nutritive and non-nutritive routes (Clark et al 2006;Clark 2008;Durham et al 2010), as reduced nutritive blood flow may contribute to the anabolic resistance observed with ageing Wilkes et al 2009). We have previously shown that in young individuals pharmacological enhancement of 'nutritive' muscle microvascular blood flow was not associated with increases in muscle protein synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to total limb blood flow, another mediator of insulin and AA delivery to the muscle is the distribution of blood flow between so-called nutritive and non-nutritive routes (Clark et al 2006;Clark 2008;Durham et al 2010), as reduced nutritive blood flow may contribute to the anabolic resistance observed with ageing Wilkes et al 2009). We have previously shown that in young individuals pharmacological enhancement of 'nutritive' muscle microvascular blood flow was not associated with increases in muscle protein synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Commonly a field of about 1 mm 2 on the dorsal nail fold of a finger is studied using an optical microscope. Perfused capillaries are counted before and after a provocation, such as arterial occlusion with a finger cuff (Clark, 2008). Only the capillaries filled with RBC will be visualised, with the risk of the true number of capillaries being underestimated.…”
Section: Capillary Microscopymentioning
confidence: 99%
“…Detailed studies in experimental animal models of diabetes support this mechanism [17], whereas the evidence in humans is indirect and probably relevant to pharmacological insulin concentrations. Nevertheless, the hypothesis that endothelial dysfunction contributes to the cellular insulin resistance of obesity or hypertension, when directly tested in vivo in man [18,19], has not been confirmed.…”
Section: What Came Afterwardsmentioning
confidence: 99%